2022
DOI: 10.4269/ajtmh.21-0948
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Polymorphisms in the Beta-Tubulin Gene and Its Relationship with Treatment Response to Albendazole in Human Soil-Transmitted Helminths in Southern Mozambique

Abstract: Soil-transmitted helminth (STH) cornerstone control strategy is mass drug administration (MDA) with benzimidazoles. However, MDA might contribute to selection pressure for anthelmintic resistance, as occurred in livestock. The aim of this study is to evaluate the treatment response to albendazole and the relationship with the presence of putative benzimidazole resistance single-nucleotide polymorphisms (SNPs) in the β-tubulin gene of STH in Southern Mozambique. After screening 819 participants, we conducted a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The presence of the common resistance markers in human STHs further provides compelling evidence for how patterns of resistance in veterinary parasites can emerge in related human parasites (O'Halloran 2021 ). What is currently uncertain is whether any of these SNPs are influencing BZ efficacy against human STHs (Furtado et al 2019 ; Grau-Pujol et al 2022 ; Matamoros et al 2019 ; Orr et al 2019 ; Zuccherato et al 2018 ). However, Diawara et al ( 2013 ) concluded that ALB exerts selection pressure on the β-tubulin gene at position 200 in T. trichiura , which could explain the moderate ALB efficacy against human trichuriasis.…”
Section: Resistance To Ahsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of the common resistance markers in human STHs further provides compelling evidence for how patterns of resistance in veterinary parasites can emerge in related human parasites (O'Halloran 2021 ). What is currently uncertain is whether any of these SNPs are influencing BZ efficacy against human STHs (Furtado et al 2019 ; Grau-Pujol et al 2022 ; Matamoros et al 2019 ; Orr et al 2019 ; Zuccherato et al 2018 ). However, Diawara et al ( 2013 ) concluded that ALB exerts selection pressure on the β-tubulin gene at position 200 in T. trichiura , which could explain the moderate ALB efficacy against human trichuriasis.…”
Section: Resistance To Ahsmentioning
confidence: 99%
“…F167Y, F200Y, E198A PCR and sequencing N. americanus Low Ghana (Orr et al 2019 ) 6. F167Y, F200Y, E198A PCR and pyrosequencing T. trichiura , N. americanus x Mozambique (Grau-Pujol et al 2022 ) 7. F167Y, E198A, E198L, F200Y Deep amplicon sequencing A. lumbricoides , A. suum x Ethiopia, Tanzania, Belgium (Roose et al 2021 ) 8.…”
Section: Resistance To Ahsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, of the three major soil-transmitted helminthiases, current drugs have the lowest efficacy for trichuriasis [4,5]. Furthermore, there is worrying evidence of resistance to mebendazole and albendazole in Trichuris in humans [6,7].…”
Section: Introductionmentioning
confidence: 99%